Mechanism of action of 4-phenoxyphenoxyethyl thiocyanate (WC-9) against Trypanosoma cruzi, the causative agent of Chagas' disease - Urbina, J.A. (2003)
We investigated the molecular basis of the activity of 4-phenoxyphenoxyethyl thiocyanate (WC-9) against Trypanosoma cruzi, the etiological agent of Chagas' disease. We found that growth inhibition of T. cruzi epimastigotes induced by this compound was associated with a reduction in the content of the parasite's endogenous sterols due to a specific blockade of their de novo synthesis at the level of squalene synthase.